The Constitutional Court and Consolidation of Democracy in Indonesia - Eddyono, Luthfi Widagdo (Mahkamah Konstitusi Republik Indonesia, 2018)
The amendment of 1945 Constitution was stipulated and conducted gradually and became one of the agendas of the Meetings of the People’s Consultative Assembly (Majelis Permusyawaratan Rakyat) from 1999 until 2002. It happened after the resignation of President Soeharto on May 21, 1998, that already in power for almost 32 years. In the reform era, Indonesia has taken comprehensive reform measures by bringing the sovereignty back to the hand of the people. To safeguard the supremacy of the 1945 Constitution, the Constitutional Court of Indonesia is formed as one of the judiciary authority organizing court proceedings to enforce the law and justice. This article analyzes the consolidation of democracy in Indonesia, the role of Constitutional Court of Indonesia based on its authority and describe how its decision has significant support for consolidation of democracy in Indonesia. The result of the research then shows that the Constitutional Court has made a positive influence in Indonesian consolidation of democracy. The Constitutional Court is also handy for upholding the constitutional norm, especially about state institutions and human rights. The Constitutional Court has taken an essential role in the consolidation of democracy in Indonesia through its decisions in judicial review of acts and resolving election disputes.